Peritonismus - Kalac, J; Veverková, L (Rozhledy v chirurgii, 1999)
The authors discuss clinic symptoms, reminding of acute abdomen, which called peritonism. Two patients admitted and treated at the 1st Department of Surgery are presented. These patients meet the criteria of the category of peritonism.
Keywords: Peritonitis; senioři; diferenciální diagnóza; Diagnosis, Differential; mužské pohlaví; ženské pohlaví; akutní bolest břicha; Humans; Female; Aged; peritonitida; Abdomen, Acute; lidé; Male